Characterization of extended-spectrum beta-lactamase-producing Enterobacteriaceae from recreational water in Athens, GA, using an undergraduate laboratory module - Coralis Rodriguez-Garcia; Helen Wall; Elizabeth Ottesen; Julie Grainy (Journal of Microbiology & Biology Education)
ABSTRACT We present a laboratory module that uses isolation of antibiotic-resistant bacteria from locally collected stream water samples to introduce undergraduate students to basic microbiological culture-based and molecular techniques. This module also educates them on the global public health threat of antibiotic-resistant organisms. Through eight laboratory sessions, students are involved in quality testing of water sources from their neighborhoods, followed by isolation of extended-spectrum beta-lactamase-producing Enterobacteriaceae. By the end of the module, students should be able to isolate Enterobacteriaceae from the environment using selective and differential media, identify isolates using biochemical tests, characterize antibiotic resistance phenotypes using Kirby Bauer and MIC tests, and evaluate the presence of select beta-lactamase genes of interest using PCR. To complement laboratory sessions, students participated in a weekly flipped classroom session with collaborative peer discussions and activities to reinforce concepts applied in the laboratory. Learning outcomes were measured over four semesters with concept checks, in-lecture activities, exams, and laboratory reports. We hypothesized that more than 50% of the student population would achieve each learning objective through the implementation of this authentic research laboratory module. Here, we highlight specific questions used to assess learning objective comprehension and demonstrate that each learning objective was achieved by 65%–100% of the student population. We present a ready-to-adapt module with flexible resources that can be implemented in courses across disciplines in biology, microbiology, environmental sciences, and public health.